Circulating levels of inflammatory cytokines and angiogenesis-related growth factors in patients with osteoarthritis after COVID-19 - Krenytska, Daryna; Strubchevska, Kateryna; Kozyk, Marko; Vovk, Tetiana; Halenova, Tetiana; Kot, Larysa; Raksha, Nataliia; Savchuk, Olexii; Falalyeyeva, Tetyana; Tsyryuk, Olena; Ostapchenko, Liudmyla (Frontiers in Medicine, 2023)
Background The disease COVID-19, caused by SARS-CoV-2 infection, has a systemic effect and is associated with a number of pathophysiological mechanisms that mobilize a wide range of biomolecules. Cytokines and growth factors (GFs) are critical regulators of tissue damage or repair in osteoarthritis (OA) and are being recognized as key players in the pathogenesis of COVID-19. A clear understanding of the long-term consequences of SARS-CoV-2 infection, especially in patients with concomitant chronic diseases, is limited and needs to be elucidated. The study aimed to evaluate the degree of inflammation and levels of pro-angiogenic and hypoxic factors, as well as heat shock proteins HSP60 and HSP70 in plasma, of patients with OA after recovery from COVID-19. Methods The research involved patients of an orthopedic specialty clinic aged 39 to 80 diagnosed with knee OA. All examined patients were divided into three groups: the Control group included conditionally healthy donors, group OA included patients with knee OA mainly stage II or III and the group of OA and COVID-19 included patients with OA who had COVID-19. The plasma levels of pro-inflammatory molecules IL-1β, IL-6, TNF-α, NF-κB, angiogenic factors VEGF, FGF-2, PDGF, hypoxic factor HIF-1α and molecular chaperones HSP60 and HSP70 were measured by enzyme-linked immunosorbent assay. Results The study showed that in both groups of patients, with OA and convalescent COVID-19, there was an increase in the plasma level of IL-1β and a decrease in TNF-α and NF-κB levels when compared to healthy controls. Systemic deregulation of the cytokine profile was accompanied by reduction in plasma levels of pro-angiogenic growth factors, most pronounced in cases of VEGF and PDGF. This analysis did not reveal any significant difference in the plasma level of HIF-1α. A decrease in the level of stress protein HSP60 in the blood of patients with OA, as well as those patients who have had SARS-CoV-2 infection, has been established. Conclusion The results suggest the potential role pro-inflammatory cytokines and angiogenesis-related growth factors in pathogenesis of both joint pathologies and long-term systemic post-COVID-19 disorders.